2008
DOI: 10.1029/2008gl034581
|View full text |Cite
|
Sign up to set email alerts
|

Dust iron dissolution in seawater: Results from a one‐year time‐series in the Mediterranean Sea

Abstract: [1] A better comprehension of atmospheric iron dissolution in seawater would be a key advance in understanding the atmospheric supply of iron to the ocean and its role on marine biogeochemistry. So far, different studies have demonstrated that dissolution of atmospheric iron depends on physical and chemical properties of the particles, which can be modified during their transport from the source. Here, based on a one-year time-series in the Western Mediterranean Sea, we show that dissolution of iron from a Sah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 25 publications
5
79
1
1
Order By: Relevance
“…The difference between these two depends on total ligands and Fe concentration. Assuming a ligand concentration of 3 µmol m −3 measured at the JGOFS-DYFAMED time-series station in June 2006 (Wagener et al, 2008), combined with the same dust addition as in DUNE, a critical concentration of ∼3.4 µmol m −3 results from Eq. (7), indicating that dust deposition could act as DFe source much longer in a system with high ligand abundance.…”
Section: Role Of Dust Deposition In Iron Replete Watersmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between these two depends on total ligands and Fe concentration. Assuming a ligand concentration of 3 µmol m −3 measured at the JGOFS-DYFAMED time-series station in June 2006 (Wagener et al, 2008), combined with the same dust addition as in DUNE, a critical concentration of ∼3.4 µmol m −3 results from Eq. (7), indicating that dust deposition could act as DFe source much longer in a system with high ligand abundance.…”
Section: Role Of Dust Deposition In Iron Replete Watersmentioning
confidence: 99%
“…In lab studies, increasing leaching time results in increases in Fe dissolution (Bonnet and Guieu, 2004) indicating that Fe dissolution is a multi-timescale process. Wagener et al (2008) studied the dissolution kinetics of Fe from dust particles and supposed one fast and one slowly dissolvable iron fraction. We introduced a dissolution timescale of 3 days into our model which represents the fast dissolution of iron.…”
Section: Chemical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A mineralogical influence has also been detected in long-term dissolution experiments. Most dust dissolution experiments are carried out over relatively short periods of time (days to weeks) but year-long in situ dissolution experiments in the Mediterranean seawater (Wagener et al, 2008) identified two pools of iron; a fast released pool which was dissolved an order of magnitude more quickly than a slow released pool (from which the rate of dissolution appeared to be controlled by organic ligands). These data convince me that there is a mineralogical control on dust dissolution and dissolution kinetics.…”
Section: Atmospheric Processing Of Aeolian Dustmentioning
confidence: 99%
“…Emission sources, such as volcanoes, biomass burning and anthropogenic sources including ship plumes (see section below), differ in composition and spatial and temporal distribution, and so establishing how each affects ocean biogeochemistry will be key to determining variability in regional response. The effect of atmospheric deposition in the surface ocean may vary with the biogeochemical state of the receiving waters, [95] and result in fundamental differences in the response of the microbial community structure (e.g. stimulation of heterotrophy v. autotrophy [96] ), and so vertical carbon export and nutrient cycling.…”
Section: Atmospheric Nutrient Supply To the Surface Oceanmentioning
confidence: 99%